ACQUISITION OF PHYSICS IN COMPREHENSIVE SCHOOL: ACCENTS OF CONSTRUCTIVISM APPROACH - Dzerviniks, Jānis; Poplavskis, Jānis (PROBLEMS OF EDUCATION IN THE 21ST CENTURY, 2012)
Nowadays in general education the emphasis is put on a pupil and his/her activity in learning. Gradually there are deepened pedagogical theories considering a pupil as an active constructor of knowledge. As the process of learning natural sciences at school is essential in the world cognition and it is needed to increase the effectiveness of learning natural sciences, including physics, as well as facilitate the attractiveness of these subjects, it is important to identify and evaluate contemporary didactic standpoints and opportunities for their application in the teaching and learning process. In the article the author analyzes the theoretical ideas of constructivism in the aspect of learning physics. The aim of the theoretical research is to evaluate the didactic standpoints of constructivism, put forward and describe the main principles of constructivism to be implemented in comprehensive secondary education. Within the research reflected in the article there is performed the analysis of scientific literature, analytical judgments are based on the previous empirical researches and using authors’ personal pedagogical experience.